Role of protein kinases JNK and p38 in regulation of mononuclear leucocytes apoptosis in oxidative stress - N. Yu. Chasovskikh (Бюллетень сибирской медицины)
Programmed cell death of peripheral blood mononuclear leucocytes taken from healthy donors and cultivated with various concentration of Н2О2, selective inhibitors of JNK (SP600125), 38 (ML3403) and in case of pneumonia was investigated. Intensification of intracellular production of reactive oxy р МАРК - gen species was accompanied by the increase in number of apoptotic and TNFR1-presented cells and mononuclears with reduced value of mitochondrial transmembrane potential in a case of oxidative stress induction with 1 mM hydrogen peroxide and in blood taken from patients with pneumonia. Action of inhibitors SP600125 and ML3403 in vitro in oxidative stress conditions prevents the increase in number of annexin- positive mononuclear cells, that confirms the participation of JNK and 38 -kinases in mechanisms of oxidative stress-mediated apoptosis dysregulation.